2015
DOI: 10.4103/0971-5916.164259
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Wolbachia from field collected Aedes albopictus Skuse in Malaysia

Abstract: Background & objectives:Wolbachia-based vector control strategies have been proposed as a mean to augment the existing measures for controlling dengue vector. Prior to utilizing Wolbachia in novel vector control strategies, it is crucial to understand the Wolbachia-mosquito interactions. Many studies have only focused on the prevalence of Wolbachia in female Aedes albopictus with lack of attention on Wolbachia infection on the male Ae. albopictus which also affects the effective expression of Wolbachia induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
2
3
1
3
Order By: Relevance
“…In our study, most populations were naturally infected with two Wolbachia strains ( w AlbA and w AlbB) at high frequencies, suggesting that superinfection is common in Ae. albopictus , as observed in other studies [ 44 , 88 , 89 , 92 ]. Interestingly, a relatively low prevalence of Wolbachia was also observed in three Ae.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, most populations were naturally infected with two Wolbachia strains ( w AlbA and w AlbB) at high frequencies, suggesting that superinfection is common in Ae. albopictus , as observed in other studies [ 44 , 88 , 89 , 92 ]. Interestingly, a relatively low prevalence of Wolbachia was also observed in three Ae.…”
Section: Discussionsupporting
confidence: 87%
“…Populations from Guangdong, Yunnan, and many sites in Hainan Province had a 100% infection rate, followed by a 90% infection rate in Henan Province in central China. Such high prevalence of Wolbachia has also been observed in other Asian countries, including Malaysia [ 43 , 88 ], Thailand [ 89 ], India [ 90 ] and Sri Lanka [ 91 ]. In our study, most populations were naturally infected with two Wolbachia strains ( w AlbA and w AlbB) at high frequencies, suggesting that superinfection is common in Ae.…”
Section: Discussionmentioning
confidence: 69%
“…However, we found that in one strain from La Reunion Island ( i.e. , Tampon), the prevalence was particularly low with respect to what detected in the other five strains and previously reported ( Noor Afizah et al, 2015 ). Moreover, in the Crema strain derived from eggs collected in 2016 in the same site used for this study, we found that 3% of the mosquitoes were uninfected.…”
Section: Discussioncontrasting
confidence: 81%
“…We found dual infection ranging from 65 to 97%. As reported by previous studies, dual infection is mainly present in females ( Joanne et al, 2015 ; Noor Afizah et al, 2015 ; Ahmad et al, 2017 ), but in two of the strains we analyzed, namely Crema and Tampon, both Wolbachia were present with higher frequency in males. A previous study that investigated w AlbA density in wild-sampled Ae.…”
Section: Discussionsupporting
confidence: 75%
“…2 ). The overall Wb infection rate (40%) found in this study lies between several field surveys around the world using field-collected specimens, which have found variable frequency rates of Wb infection ranging from 11 to 100% ( Kitrayapong et al 2002 , de Albuquerque et al 2011 , Zhang et al 2014 , Noor Afizah et al 2015 , Ahmad et al 2017 , Guo et al 2018 , Martin et al 2019 , Hu et al 2020 ).…”
Section: Resultsmentioning
confidence: 52%